2011
DOI: 10.1007/s00784-011-0520-4
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial on fluoride varnish application for treatment of white spot lesion after fixed orthodontic treatment

Abstract: The purpose of this study was to determine the efficacy of fluoride varnish (5% sodium fluoride, Duraphat®, Colgate) in reverting white spot lesions (WSLs) after fixed orthodontic treatment. This study was a randomized, parallel group, controlled clinical trial. Using saline solution as control, 110 participants (mean age ± standard deviation: 16.6±3.2 years) ranging from 12 to 22 years old were randomly assigned to either the test group (group 1) or the control group (group 2). Application of fluoride varnish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(132 citation statements)
references
References 31 publications
3
120
0
9
Order By: Relevance
“…This finding corroborates those of previous studies (6,10,12,16,18,19). There was a 45.7% reduction in WSL size, which is in agreement with previous studies (9,10,12,16).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding corroborates those of previous studies (6,10,12,16,18,19). There was a 45.7% reduction in WSL size, which is in agreement with previous studies (9,10,12,16).…”
Section: Discussionsupporting
confidence: 93%
“…Fluoride varnishes have gained popularity due to their high concentration and safety during application (8). A number of studies have demonstrated that fluoride varnishes are able to remineralize incipient carious lesions as well as prevent decay when used with other preventive measures, such as diet control and reduction of dental biofilm (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…5 Modern dentistry concentrates more on prevention of lesions than their operation. 9 Orthodontists should assess patients' risk factors throughout the treatment to prevent white spot lesions. Presence of the following factors increases the probability of white spot lesions occurrence: inappropriate oral hygiene, caries history or high decay missing filled surfaces (DMFS), and lack of preventive methods, such as fluoride or antibacterial compositions.…”
Section: Effect Of Co2 Laser and Fluoride Varnish Application On Micrmentioning
confidence: 99%
“…A very common example of this occurs immediately after removal of orthodontic brackets, whereby zones of non-cavitated demineralization developed (even as early as one month into bracket placement) about the previously bonded bracket [19,23]; however, these zones are usually able to remineralize to some extent over a month or two using standard oral hygiene practices combined with the natural remineralizing potency of saliva [23][24][25]. However, topical remineralization therapies may be used to accelerate the recovery [19,26].…”
Section: Introductionmentioning
confidence: 99%